High frequency oscillating ventilation (HFOV) in severe acute respiratory distress syndrome (ARDS): a case report - Md Ralib, Azrina; Mat Nor, Mohd Basri; Mohamed, Abdul Hadi; Lukman, Mohd Fahmi; Osman, Ariff; MY, Asmarawati (Faculty of Medicine, International Islamic University Malaysia, 2010)

(untitled)
High frequency oscillating ventilation (HFOV) provides a rescue therapy for patients with refractory hypoxaemia in severe acute respiratory distress syndrome (ARDS). HFOV utilizes high mean airway pressures to maintain an open lung and low tidal volumes at a high frequency that allows for adequate ventilation while at the same time preventing alveolar overdistension. This seems to be an ideal lung protective ventilation strategies to prevent ventilator-induced lung injury (VILI)2. We reported a case of severe extrapulmonary ARDS secondary to acute lymphoblastic leukaemia responding to the use of HFOV.